2018
DOI: 10.5430/jha.v7n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the organizational culture at a hospital in Benin

Abstract: Objective: To describe the organizational culture (OC) and its strength in a Hospital in Benin. Methods: This is a descriptive cross-sectional study which involved 121 participants (care providers, support and executive staff) of the Lokossa regional hospital in March 2015. Data on dimensions of OC were collected using a questionnaire developed from the Cameron and Quinn's tools (2006). Results: The mean age of participants was 41 ± 8.3 years and working experience was less or equal to five years in 52.07%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Moreover, it also could increase staff involvement in their work. Strong hierarchical orientation and results-based options from organizational culture as good leadership outputs can improve hospital performance (Sopoh et al, 2018).…”
Section: Effect Of Job Motivation On Nursing Performancementioning
confidence: 99%
“…Moreover, it also could increase staff involvement in their work. Strong hierarchical orientation and results-based options from organizational culture as good leadership outputs can improve hospital performance (Sopoh et al, 2018).…”
Section: Effect Of Job Motivation On Nursing Performancementioning
confidence: 99%
“…8 In low-and middle-income country (LMIC) settings, a growing body of research on organizational culture has focused on the association between hospital safety culture and patient outcomes. [12][13][14][15][16] Further, a systematic review of qualitative and ethnographic studies of public health systems in LMICs demonstrated the important role of organizational culture in the success of LMIC health sector reforms, positing that health sector redesign 17 is insufficient to achieve global health targets, and that intangible aspects of inner settings (ie, organizational culture) drive the functions, operations, and relationships within each health systems. 17 Despite this growing body of evidence supporting the role of organizational culture in efforts to strengthen health systems in LMIC settings, policy-makers and researchers lack tools to meaningfully measure organizational culture.…”
Section: Introductionmentioning
confidence: 99%